Development Of Low Frequency Electromagnetic Vibration Energy Harvester - Hairudin, Wan Masrurah (2016)
This thesis presents the development of an energy harvester based on electromagnetic system to harvest energy from the low frequency vibration in particular structural vibration of the bridge. The eventual intended application is to power up a wireless sensor node that can be used to monitor structural integrity of a bridge. The electromagnetic vibration energy harvester is developed with four units of voice coil actuators using Neodymium magnets and copper coils. An open circuit voltage of 2.6 V and maximum output power of 25 mW were generated at 10 Hz under constant acceleration of 0.35g respectively. A model of the harvester is made by combining the mechanical of mass-spring-damper system with the electromagnetic resistance and inductance where the velocity of the moving coil from the mechanical system will produce current in the system. The simulation model showed a good agreement with the experimental results at 4 - 10 Hz for one cell harvester with 4.3% difference. The main contribution of this research is the prototype construction of low vibration energy harvester system and development of the energy harvester model using Simulink. The power density of the harvester system is 602 μW/g.cm3 and 1308.2 μW/g.cm3 at 4 Hz and 10 Hz respectively and enough to power up the wireless sensor network device.